1982
DOI: 10.1002/ddr.430020308
|View full text |Cite
|
Sign up to set email alerts
|

Renal vasodilators and hypertension

Abstract: SK&F 82526 is a potent renal vasodilator in dogs, monkeys, and hypertensive rats. It is orally active and has a specificity for the renal vasculature greater than dopamine. Its activity is owing, at least in part, to stimulation of renal dopamine receptors and has no effect on a-or p-adrenergic receptors. This compound should be valuable in further examining the importance of renal blood flow in essential hypertension.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
17
0

Year Published

1983
1983
1991
1991

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(19 citation statements)
references
References 28 publications
2
17
0
Order By: Relevance
“…In this paper, we will present our current understanding ofthe pathogenesis ofarterial lesions caused in the rat by fenoldopam mesylate (FM), a selective post-junctional dopaminergic DA l agonist (10, 21-23, 26, 29, 32), and dopamine, an alpha-adrenergic, beta-adrenergic, and dopaminergic agonist (1,9,17,25,31). FM-induced arterial lesions originally reported by Morgan and Yuhas (19,35), were only observed in the rat, and only after continuous intravenous infusion for 24 hr at doses ranging from 1 to 100~g/kg/min.…”
Section: Introductionmentioning
confidence: 99%
“…In this paper, we will present our current understanding ofthe pathogenesis ofarterial lesions caused in the rat by fenoldopam mesylate (FM), a selective post-junctional dopaminergic DA l agonist (10, 21-23, 26, 29, 32), and dopamine, an alpha-adrenergic, beta-adrenergic, and dopaminergic agonist (1,9,17,25,31). FM-induced arterial lesions originally reported by Morgan and Yuhas (19,35), were only observed in the rat, and only after continuous intravenous infusion for 24 hr at doses ranging from 1 to 100~g/kg/min.…”
Section: Introductionmentioning
confidence: 99%
“…SKF 82526-J stimulates dopamine-sensitive adenylate cyclase in the rat caudate nucleus, an effect blocked by the dopamine antag- onists haloperidol, chlorpromazine, and bulbocapnine (13). SKF 82526-J has -3.5-fold the potency of dopamine in renal vasodilation in the dog, an effect also blocked by the dopamine antagonists, bulbocapnine and metoclopramide (13)(14)(15)(16). The compound is devoid of alpha-or beta-adrenergic receptor stimulating activity, is well absorbed orally, and does not cross the blood-brain barrier (13)(14)(15)(16).…”
Section: Introductionmentioning
confidence: 99%
“…SKF 82526-J has -3.5-fold the potency of dopamine in renal vasodilation in the dog, an effect also blocked by the dopamine antagonists, bulbocapnine and metoclopramide (13)(14)(15)(16). The compound is devoid of alpha-or beta-adrenergic receptor stimulating activity, is well absorbed orally, and does not cross the blood-brain barrier (13)(14)(15)(16). SKF 82526-J does not inhibit nerve-evoked norepinephrine release (13,14).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Preliminary studies in animals9 10 and patients"1 have indicated that it acts through stimulation of specific postsynaptic dopamine receptors in the renal vascular bed. However, unlike dopamine, higher doses of fenoldopam do not seem to increase either blood pressure or heart rate.9 This study was designed to determine the systemic and regional hemodynamic, cardiac, reflexive, and biochemical effects of a single oral dose of fenoldopam in patients with essential hypertension.…”
mentioning
confidence: 99%